(untitled) (International Journal of Engineering and Computer Science, 2015)
Ontologies are used in various fields such as knowledge management, information extraction and semantic web. From the point of view of a particular criterion of application, the problem mainly faced is to determine that which of the ontologies would best suit a particular problem. The (re)use of ontologies without anomalies is a critical point in the industrial area in order to produce successful projects; hence the selection of an evaluation technique is mandatory. This paper presents the comparison of various evaluation methods based on different parameters that will help the users to select the best one based on the situation they are in.